Pengembangan Modul Matematika Siswa Berbasis Pendekatan PMRI Pada Materi Bangun Datar Kelas IV Sekolah Dasar - Heru, Heru; Yuliani, Refi Elfira; Giastuti, Ayun (Universitas Muhammadiyah Palembang, 2019)
Student-centred learning requires teachers to provide learning materials that can support learning activities. This is so students can actively learn about learning resources and group discussions to gain knowledge. The obstacle issued by the teacher in making teaching materials themselves is the time required to create teaching materials. The development of modules based on PMRI learning provides a new colour in learning activities and the provision of teachers and activities in learning that are oriented towards student-centred learning. The research used is development research (development research) that uses a device development model design, according to Thiagarajan, namely defining, designing, developing, and disseminating. Based on the validity test from the experts and filling in the student questionnaire when the trial was limited, the score obtained was a percentage of 90.14% so that it can be concluded that the student module was based on PMRI's